Aorto-duodenal fistula secondary to aortic graft replacement. Issue 1 (2nd January 2022) - Vandermeulen, Morgan; Verscheure, Dorian; Genser, Laurent
Abstract: Secondary aorto-duodenal fistula (SADF) is a rare and serious event occurring in up to 45% of aortic prosthesis infections. The clinical manifestations are variable ranging from isolated signs of graft infection such as fever to massive gastrointestinal bleeding. The diagnosis is based on CT scan and is generally oriented by an inconstant association of indirect signs. Despite a high early severe postoperative morbidity and mortality, especially in presence of a preoperative shock, emergency surgery allows for the diagnosis and treatment of SADF with multidisciplinary management allowing favorable midterm outcomes among surviving patients. The images that we present in this manuscript highlight some indirect signs of SADF on CT scan that should alert clinicians to warrant on time surgical management with an illustration of per operative diagnosis of the fistula.